2016
DOI: 10.3390/dj4040039
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Diagnosis of Osteonecrosis of the Jaw (ONJ) Associated with Bevacizumab Therapy in Colorectal Cancer Patients: Report of Two Cases

Abstract: Medication-induced Osteonecrosis of the Jaw (MRONJ) has been reported not only after use of antiresorptive agents (bisphosphonates and denosumab), but also in cancer patients receiving antiangiogenic agents, alone or combined with antiresorptive drugs. We report two cases of MRONJ observed in colorectal cancer patients after bevacizumab therapy only. MRONJ was diagnosed, respectively, two and seven months after a tooth extraction; both the patients had received two courses of bevacizumab infusions (for a total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…Notably, the 2009 American Association of Oral and Maxillofacial Surgeons (AAOMS) criteria (Ruggiero et al., ) were expanded to include all anti‐resorptives and anti‐angiogenics in 2014 (Ruggiero et al., ), but the 2015 International Taskforce on Osteonecrosis of the Jaw (ITONJ) consensus paper again removed anti‐angiogenics due to a lack of evidence (Khan et al., ). As reports of osteonecrosis of the jaw in patients receiving anti‐angiogenics or chemotherapy without a prior history of anti‐resorptive therapy gradually accumulate (Erovigni et al., ; Estilo et al., ; Koch, Walter, Hansen, Jäger, & Wagner, ; Nicolatou‐Galitis et al., ; Viviano, Rossi, & Cocca, ) Aghaloo & Tetradis, ; DeSesa, Appugounder, Haberland, & Johnson, ; Infante‐Cossio, Lopez‐Martin, Gonzalez‐Cardero, Martinez‐de‐Fuentes, & Casas‐Fernandez‐Tejerina, ; Nicolatou‐Galitis et al., ), a comprehensive review of the literature is necessary to establish which patients are at risk of MRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, the 2009 American Association of Oral and Maxillofacial Surgeons (AAOMS) criteria (Ruggiero et al., ) were expanded to include all anti‐resorptives and anti‐angiogenics in 2014 (Ruggiero et al., ), but the 2015 International Taskforce on Osteonecrosis of the Jaw (ITONJ) consensus paper again removed anti‐angiogenics due to a lack of evidence (Khan et al., ). As reports of osteonecrosis of the jaw in patients receiving anti‐angiogenics or chemotherapy without a prior history of anti‐resorptive therapy gradually accumulate (Erovigni et al., ; Estilo et al., ; Koch, Walter, Hansen, Jäger, & Wagner, ; Nicolatou‐Galitis et al., ; Viviano, Rossi, & Cocca, ) Aghaloo & Tetradis, ; DeSesa, Appugounder, Haberland, & Johnson, ; Infante‐Cossio, Lopez‐Martin, Gonzalez‐Cardero, Martinez‐de‐Fuentes, & Casas‐Fernandez‐Tejerina, ; Nicolatou‐Galitis et al., ), a comprehensive review of the literature is necessary to establish which patients are at risk of MRONJ.…”
Section: Introductionmentioning
confidence: 99%
“…The mean age of patients with AARONJ was 59.7 years, and the median, 60 years, with minimum age of 47 years ( 3 ) and maximum age of 79 years. ( 4 ) In respect to sex, 11 patients were male (58%) ( 2 4 , 10 , 14 17 , 19 ) and 8 were female (42%); ( 1 , 5 , 6 , 8 , 9 , 12 , 13 , 16 , 18 ) different from what the AAOMS reported in 2014. ( 7 ) The race of patients was not described in the articles and, therefore, was excluded from the final result table.…”
Section: Discussionmentioning
confidence: 77%
“…In this review, we observed that antiangiogenic agents were prescribed for metastatic cancer in 63.2% (n=12) of cases, ( 1 5 , 10 13 , 17 , 18 ) whereas kidney cancer was the most prevalent diagnosis (n=6; 31.6%), ( 4 , 6 , 11 , 13 , 15 , 17 ) followed by colon cancer, with 15.8% (n=3). ( 2 , 4 , 5 ) Antiangiogenic agent-related osteonecrosis of the jaws was also described in a non-cancer case of retinal vein thrombosis. ( 14 )…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations